New Phlugidia species (Orthoptera: Tettigoniidae: Meconematinae, Phlugidini) from the Eastern Arc Mountains of Tanzania, Africa - Hemp, Claudia (Zootaxa, 2013)
Two new species of Phlugidia (Orthoptera: Tettigoniidae: Meconematinae) are described from the Eastern Arc Mountains of Tanzania. P. planicercus Hemp n. sp. occurs in lowland forest at the foothills of the Uluguru Mountains, while P. ob-tusicercus Hemp n. sp. was collected in the Nguru Mountains. A key to Phlugidia species is provided.